Carob trees (Ceratonia siliqua L.) regenerated in vitro can acclimatize successfully to match the field performance of seed-derived plants - Osório, Maria Leonor (2014)
The use of in vitro regenerated plants in forestry and orchard depends ultimately on the development of efficient transplantation protocols, ensuring high survival rates and successful establishment under field conditions. We tested the performance of micropropagated carob trees (Ceratonia siliqua L.) throughout the acclimatization process in terms of survival, growth and physiological traits, including field comparisons with seed-derived and mother plants. The field trial was 100 %successful, i.e. we found no major differences between micropropagated, seed-derived and mother plants in terms of growth rate, height, number of leaves, photosynthetic efficiency, chlorophyll fluorescence, chlorophyll content and soluble protein content, although these parameters changed significantly during acclimatization. Stomatal conductance (gs) was reduced by fourfold when plants were transferred from in vitro culture to the growth chamber, thus preventing uncontrolled wilting. The photosynthetic rate (PN) was relatively low in vitro, in the growth chamber and the greenhouse, but increased to match seed-derived and mother plants in the field. The chlorophyll a/b ratio in leaves from in vitro and growth chamber plants was typical of shade plants (2.1) but became more characteristic of sun plants in the subsequent acclimatization stages (3.1–3.5). The maximum efficiency of photosystem II (Fv/Fm) remained mostly constant at ~0.80 throughout acclimatization, as is typical for healthy, non-stressed plants. We conclude that our micropropagation and acclimatization protocols provide a suitable alternative to traditional mass propagation techniques for the carob tree.